The Contributions of Pharmacy to the Improvement of Community Health: Turning Points and Experiences from Serbia in the XX Century - Krajnović, Dušanka (Archives of Pharmacy, 2022)
Тhis paper analysed three turning points in the development of apothecary sector in Serbia in the last century, by using the method of documentary analysis. Changes in the structure of apothecary network were monitored through the issues of ownership, personnel and products assortment. Separation of the field of apothecary work from the wholesale drugstores, retail pharmacies and shops by numerous regulations adopted in 1930s, pharmacy became a public health institution with precise, but extensive list of products that can be sold in addition to medicines. However, the socialization of pharmacies initiated with the confiscation and the sequestration of private pharmacies (1946, 1949), led to changes in the assortment of products, mostly medicines (compounded, galenics and patent medicines). In the next thirty years, several organizational solutions were changed; the development of pharmacy network within the health care system was systematic; the staff increased; and the focus was on medicines` availability. From 1950 to 1980, the number of pharmacists and technicians will triple, and the network will extend in the rural areas (with 468 pharmacies and 288 apothecary stations). The introduction of private ownership, without restrictions to the masters of pharmacy and the lack of opening criteria in 1990s, led to unplanned expansion of the network in private sector, without sufficiant increase in staff. Additionly, an expansion of the health-related products outside the category of medicine were characteristic.